2016
DOI: 10.1016/j.bpj.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Binding Mechanism of the N-Terminal SH3 Domain of CrkII and Proline-Rich Motifs in cAbl

Abstract: The N-terminal Src homology 3 (nSH3) domain of a signaling adaptor protein, CT-10 regulator of kinase II (CrkII), recognizes proline-rich motifs (PRMs) of binding partners, such as cAbl kinase. The interaction between CrkII and cAbl kinase is involved in the regulation of cell spreading, microbial pathogenesis, and cancer metastasis. Here, we report the detailed biophysical characterizations of the interactions between the nSH3 domain of CrkII and PRMs in cAbl. We identified that the nSH3 domain of CrkII binds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 80 publications
6
41
0
Order By: Relevance
“…Src 49 ). Crk, a scaffold protein consisting of a tandem SH2-SH3-SH3, binds through its middle SH3 domain to the proline-rich Crk-binding sites located at the disordered C-terminal tail of Abl 50,51 (Fig. 1a) and uses its SH2 domain to bind to the linker SH2-KD (ref 52).…”
Section: Resultsmentioning
confidence: 99%
“…Src 49 ). Crk, a scaffold protein consisting of a tandem SH2-SH3-SH3, binds through its middle SH3 domain to the proline-rich Crk-binding sites located at the disordered C-terminal tail of Abl 50,51 (Fig. 1a) and uses its SH2 domain to bind to the linker SH2-KD (ref 52).…”
Section: Resultsmentioning
confidence: 99%
“…All protein samples for crystallization, fluorescence, and NMR experiments were prepared as described elsewhere (12). Synthetic peptides were purchased in a crude form and further purified using reverse-phase highperformance liquid chromatography in our laboratory.…”
Section: Protein and Peptidesmentioning
confidence: 99%
“…The binding affinity of the nSH3 domain with PRM NS1 is significantly higher than its interactions with other cellular binding partners. For example, the nSH3 domain binds PRM NS1 with $3000-fold higher affinity than the PRM of JNK1 (11,12). It was suggested that the high affinity is due to long-range electrostatic interactions between positively charged residues in PRM NS1 and a negatively charged binding interface in the nSH3 domain (11).…”
Section: Introductionmentioning
confidence: 99%
“…The above results showed that promiscuous binding of peptide molecule can be effectively ameliorated by rational design. Based on various public crystallographic data, [33][34][35][36][37][38] the SH3 domain has been thoroughly researched and broadly recognized as one of the best available systems for the examination of ligand-protein interactions. For example, Larson et al constructed a diverse alignment of SH3 domain sequences.…”
Section: Implication Of the Current Resultsmentioning
confidence: 99%